Evaluation of patients’ knowledge about prostate gland mild expansion - Sierżantowicz, Renata; Dreger, Marta; Łagoda, Katarzyna; Jurkowska, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. Benign prostatic hyperplasia (BPH) is one of the most common disorders diagnosed in men over fifty years old. Health education has a great impact on the BPH therapeutic and nursing care. It should indicate risk factors of the disease in order to delay its development and prepare patients to self-care and self-control. Aim of the study. Evaluation of the patients’ level of knowledge about benign prostatic hyperplasia and determining the demand for health education. Material and methods. The study was conducted among one hundred patients suffering from benign prostatic hyperplasia a standardized method (International Prostatic Symptom Score) and a self-constructed questionnaire were used as examination methods. Results. The main results were as follows. Half of the respondents were between sixty and seventy years old. Thirty five per cent of respondents claimed that a nurse informed them about the preparation for the treatment and the examination as well as about the medicine intake. On the other hand, thirty five per cent of patients stated that nobody educated them at all. Almost majority of the questioned (97%) declared that BPH patients’ education has an influence on the decrease of symptoms. Conclusions. Patients’ level of knowledge about benign prostatic hyperplasiais not sufficient. Patients expect information about the source of the BPH disease, its symptoms and ways of treatment.